Doug C. answered • 16d

Math Tutor with Reputation to make difficult concepts understandable

desmos.com/calculator/unoht7oj7i

Anne B.

asked • 16dEquation: log(2x-5) + log(x-3) = 1

Once stated and explained the restriction(s), include a solution to the equation in your response.

Follow
•
2

Add comment

More

Report

Doug C. answered • 16d

Tutor

5.0
(1,228)
Math Tutor with Reputation to make difficult concepts understandable

desmos.com/calculator/unoht7oj7i

Yefim S. answered • 16d

Tutor

5
(20)
Math Tutor with Experience

2x - 5 > 0 and x - 3 > 0

x > 2.5 and x > 3.

So, x > 3 (1)

log[(2x - 5)(x - 3)] = 1;

So, 2x^{2 }- 11x + 15 = 10; 2x^{2} - 11x + 5 = 0; (x - 5)(2x - 1) = 0; x = 5 or x = 1/2

From (1) we have to reject x = 1/2.

Answer: x = 5

2x-5> 0

2x>5

x> 5/2

x-3 > 0

x > 3

x = about 4

if you interpret log as natural log. While ln is used for natural log, log itself can be used that way too. Although in early math courses log tends to be a common log with base 10

ln(2(4)-5) = ln3 = a little less than 1.1

ln(4-3) = ln1 = 0

1.1 + 0 is close to 1

If you intended to use log as base 10

then log(2(5)-5) = log5 = about 0.7

and log(5-3) = log2 = about 0.3

.7+.3 = 1

for natural log, with base e, the solution to the equation is about 4

for common log, with base 10, the solution is 5

Ask a question for free

Get a free answer to a quick problem.

Most questions answered within 4 hours.

Find an Online Tutor Now

Choose an expert and meet online. No packages or subscriptions, pay only for the time you need.